2008
DOI: 10.1242/dev.010744
|View full text |Cite
|
Sign up to set email alerts
|

A novel promoter-tethering element regulates enhancer-driven gene expression at the bithorax complex in theDrosophilaembryo

Abstract: A key question in our understanding of the cis-regulation of gene expression during embryonic development has been the molecular mechanism that directs enhancers to specific promoters within a gene complex. Promoter competition and insulators are thought to play a role in regulating these interactions. In the bithorax complex of Drosophila, the IAB5 enhancer is located 55 kb 3′ of the Abdominal-B(Abd-B) promoter and 48 kb 5′ of the abdominal-A(abd-A) promoter. Although roughly equidistant from the two promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…An intriguing possibility is that the larger ct enhancer fragment could possess sequences that aid in targeting distal promoters, including promoters in trans, that are not present in the smaller fragment. Indeed, the ct enhancer is normally 80 kb away from its promoter target, and sequences that promote long-range enhancer-promoter interactions in cis and in trans have been characterized for other genes (Hopmann et al 1995;Zhou and Levine 1999;Calhoun et al 2002;Calhoun and Levine 2003;Lin 2003;Akbari et al 2008;Fujioka et al 2009;Majumder et al 2015). The notion that variation in transvection could be partially dependent on factors beyond enhancer strength is supported by previous studies.…”
Section: Factors Other Than Enhancer Strength Influence Transvectionmentioning
confidence: 84%
See 1 more Smart Citation
“…An intriguing possibility is that the larger ct enhancer fragment could possess sequences that aid in targeting distal promoters, including promoters in trans, that are not present in the smaller fragment. Indeed, the ct enhancer is normally 80 kb away from its promoter target, and sequences that promote long-range enhancer-promoter interactions in cis and in trans have been characterized for other genes (Hopmann et al 1995;Zhou and Levine 1999;Calhoun et al 2002;Calhoun and Levine 2003;Lin 2003;Akbari et al 2008;Fujioka et al 2009;Majumder et al 2015). The notion that variation in transvection could be partially dependent on factors beyond enhancer strength is supported by previous studies.…”
Section: Factors Other Than Enhancer Strength Influence Transvectionmentioning
confidence: 84%
“…Interactions have been identified between sequences on the same chromosome (in cis) or on different chromosomes (in trans) (Lieberman-Aiden et al 2009;Duan et al 2010;Sexton et al 2012;van de Werken et al 2012;Nagano et al 2013;Zhang et al 2013). Many long-distance interactions in cis underlie the activation of specific genes, and in some cases, sequences have been identified that facilitate interactions between a distal enhancer and a specific promoter target (Zhou and Levine 1999;Calhoun et al 2002;Calhoun and Levine 2003;Lin 2003;Akbari et al 2008;Fujioka et al 2009;Majumder et al 2015). In contrast, the genetic impacts of trans-interactions between chromosomes are less clearly understood.…”
mentioning
confidence: 99%
“…63,64 and Drosophila genes. 51,[65][66][67][68][69][70] In the proximity hypothesis we posit that (1) pGawB but not PlacW or PGalW require proximity to promoter proximal elements in order to report the full spectrum of enhancer activity and that (2) omb P3 inserted at around 1.5 kb upstream of exon I does profit from such elements whereas omb P4 inserted 12 kb downstream of exon I and 2 kb upstream of exon Ia does not.…”
Section: Discussionmentioning
confidence: 99%
“…Insulators isolate enhancers from nearby genes, restricting their influence to the target core promoter(s) (Bell et al, 2001). Last but not least, promoter-tethering elements facilitate the interaction between enhancers and target core promoters (Akbari et al, 2008).…”
Section: Introductionmentioning
confidence: 99%